2021
DOI: 10.1002/14651858.cd013674.pub2
|View full text |Cite
|
Sign up to set email alerts
|

New generation antidepressants for depression in children and adolescents: a network meta-analysis

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 186 publications
1
62
1
1
Order By: Relevance
“…23 A recent Cochrane review found no antidepressant had a clinically significant effect compared with placebo, leading the authors to question 'whether they should be used at all', especially considering some antidepressants increased suicide risk compared with placebo in this population. 24 Re-analysis of original clinical study reports from adolescent trials suggests that the published accounts of studies exaggerated benefits (for example, by switching reporting to outcomes not specified in the protocol) and under-reported risks (for example, by coding suicide attempts in the antidepressant group as 'emotional lability'). 23 25 The number of 12-to 17-year-olds prescribed antidepressants more than doubled between 2005 and 2017.…”
Section: Questions Relating To Efficacymentioning
confidence: 99%
“…23 A recent Cochrane review found no antidepressant had a clinically significant effect compared with placebo, leading the authors to question 'whether they should be used at all', especially considering some antidepressants increased suicide risk compared with placebo in this population. 24 Re-analysis of original clinical study reports from adolescent trials suggests that the published accounts of studies exaggerated benefits (for example, by switching reporting to outcomes not specified in the protocol) and under-reported risks (for example, by coding suicide attempts in the antidepressant group as 'emotional lability'). 23 25 The number of 12-to 17-year-olds prescribed antidepressants more than doubled between 2005 and 2017.…”
Section: Questions Relating To Efficacymentioning
confidence: 99%
“…It was found that antidepressants were associated with a greater risk of suicide-related events than placebo (OR 1.58, 95%CI 1.02-2.45; 17 studies; n=3229; low quality of evidence). In 2021 the same author published a new review concerning children and adolescents with major depressive disorder in which the effect of different types of antidepressants was analysed separately 22 . Statistically significant differences were only found for venlafaxine, which showed an increase in suicide-related events: OR 13.84, 95%CI (1.79-106.90) (low quality of evidence).…”
Section: Suicidalitymentioning
confidence: 99%
“…A higher risk of serious adverse events was fond with SSRIs (RR 1.71 95%CI 1. 22 Atomoxetine is indicated for the treatment of attentiondeficit hyperactivity disorder (ADHD) in patients aged 6 years and older. However, it was initially developed as an antidepressant, and suicidal behaviours (suicide attempts and suicidal ideation) have also been reported immediately, symptoms that might be subsequently interpreted as side effects should be monitored for 7 days before prescribing.…”
Section: Serious Adverse Eventsmentioning
confidence: 99%
“… 6 Also, Hetrick et al defined ‘suicide-related behaviour’ as a collection of suicide, suicide attempt and suicidal ideation when exploring new generation antidepressants for depression in children and adolescents, with suicidal ideation rated with standardised, validated and reliable rating scales. 7 Normally, suicide-related scales were used to detect suicidal ideation, suicide attempt and suicide behaviour in many previous studies. However, several recent studies cast doubts on the validity of these scales.…”
Section: Introductionmentioning
confidence: 99%